In silico screening for identification of fatty acid synthase inhibitors and evaluation of their antiproliferative activity using human cancer cell lines. (4th July 2018) - Nisthul A., Amrutha; Retnakumari, Archana P.; A., Shabna; Anto, Ruby John; Sadasivan, C.
Abstract: De novo lipogenesis (DNL) by upregulation of fatty acid synthase (FASN) is an important metabolic alteration of cancer cells. FASN is over-expressed in several cancers and is often associated with a high risk of recurrence and poor prognosis. Differential expression of FASN in cancer cells and their normal counterparts leads to the impression that FASN can be an attractive druggable target in cancer therapy. Present study focuses on identification of inhibitors against FASN ketoacyl synthase (KS) domain from Asinex Biodesign compound database using in silico tools. Virtual screening resulted in the identification of two hit compounds BDD27845077 and BDD27845082 with a common core structure. Molecular Docking studies showed that BDD27845077 and BDD27845082 bind at the substrate entry channel of KS domain with GScore –12.03 kcal/mol and –12.29 kcal/mol respectively. Molecular dynamics (MD) simulation of the protein-ligand complexes shows the binding stability of ligands with FASN-KS. In vitro validation of BDD27845082 demonstrated that the compound possesses antiproliferative activity in a panel of human cancer cell lines including MDA-MB-231 (breast cancer), HCT-116 (colon cancer) and HeLa (cervical cancer) with maximum sensitivity against HCT-116 (IC 50 = 25 µM). The study put forward two lead compounds against FASN with favorable pharmacokinetic profile as indicated by virtual screening tools for the development of cancer chemotherapeutics.